SYNERGISTIC ACTIVITY OF ENZYMES PRODUCED BY EUPENICILLIUM JAVANICUM AND ASPERGILLUS NIGER NRRL 337 ON PALM OIL FACTORY WASTES - TRESNAWATI PURWADARIA; NONI NIRWANA; Pius P. KETAREN; DYAH ISWANTINI PRADONO; YANTYATI WIDYASTUTI (BIOTROPIA, 2003)
The use of palm kernel cake (PKC) and palm oil mill effluent (POME), substances from palm oil factory wastes, for monogastric is limited by their high cellulose and mannan contents. Hydrolytic enzymes have been supplemented to increase the nutrient digestibility. The maximal digestibility was obtained in the synergistic action of all enzyme components including B-D-endoglucanase (CMCase), B-D-glucosidase, B-D-mannanase, p-D-mannosidase, and oc-D-galactosidase. Two kinds of enzymes produced by Eupenicillium javanicum  and Aspergillus niger NRRL 337 on the submerged culture containing 3% coconut meal were selected to hydrolyze PKC or dry POME. Enzyme from E. javanicum contained higher CMCase, B-D-mannanase, and a-D-galactosidase activities, while that from  A. niger  NRRL 337 contained more p-D-glucosidase and p-D-mannosidase activities. Saccharification (hydrolytic) activities of enzyme mixtures on PKC and POME were determined at pH 5.0, the optimal pH for p-D-mannanase from  E. javanicum,  and at 5.4 the optimal pH for a-D-galactosidase from  E. javanicum  and P-D-glucosidase from  A. niger NRRL 337. The enzyme proportions of E. javanicum and A. niger NRRL 337 were 100 : 0, 80 : 20, 60 : 40, 40 : 60, and 0 : 100%. The highest Saccharification activity on both substrates was observed on the mixture of 80% A. niger NRRL 337. The pH levels did not significantly affect Saccharification activity. Fiber components in PKC were more digestable than in POME. Further analysis on the reducing sugar components using thin layer chromatography showed that more monomers were produced in the 60 or 80% of A. niger NRRL 337. The glycosidases of A. niger NRRL 337 played more important role in the Saccharification activity. Keywords:        Synergistic activity/ palm kernel cake/palm oil mill effluent/ Eupenicillium javanicum/ Aspergillus niger NRRL 337